Innovative Authentic and Formative Assessment in Science Education: A Systematic Review - Nakjah, Salwa Nur Sapiatun; Adawiah, Rabiatun (Indonesian Journal of Teacher Education, 2025)
The implementation of the Merdeka Curriculum emphasizes that assessment is an integral part of the learning process, focusing on core subjects, the Pancasila Student Profile, and providing flexibility to cultivate students’ interests and potential. Despite its importance, observations suggest that most science teachers in the field continue to employ conventional assessments that rely heavily on written examinations and summative testing. This study is a systematic literature review designed to identify and synthesize empirical and theoretical findings regarding innovations in formative and authentic assessments within science education. Data collection was conducted using rigorous and relevant inclusion and exclusion criteria, with a review of literature indexed in Scopus and Sinta from 2018 to 2025. The review findings show that innovations in authentic and formative assessments in science learning are largely driven by the use of technology, including digital platforms (PlayPosit, Canvas, Quizizz, Kahoot!), specialized models (e.g., the Science Authentic Assessment Model), as well as integration with literacy and numeracy concepts. These innovations have been demonstrated to be effective and practical in comprehensively evaluating students’ competencies, including improvements in conceptual understanding and cognitive learning outcomes, as well as enhanced motivation, participation, science process skills, and higher-order thinking skills (HOTS) within the affective and psychomotor domains. Overall, the implementation of these innovative assessment approaches supports the achievement of science learning objectives in the digital era.